DESCONSTRUINDO O “MAGO” EM SIMÃO: O ESTUDO DA MAGIA NO CRISTIANISMO PRIMITIVO, UMA ANÁLISE A PARTIR DOS ATOS DE PEDRO - LIMA, ALBERTINO DA SILVA (2017)
The presente dissertation aims to foster a centralized study on the character Simon, stigmatizated as magician by Early Christian Literature. To do that we will highlight the character introduced at chapter 8 from the Apostle´s Acts and will take a look at him, above all from the Apocryphal Acts of Peter due to the fact that this texts offers a more comprehensive picture about Simon, his spells and his duels with Peter. For this, we will use as a method, the Carlo Ginsburg´s indoctrination paradigm. With the aim of proposing clarification on the subject, this research is divided in three parts: in the first moment, we will work on the historical aspects of magic, and their sociological and anthropological concepts. In the second moment, we will discuss the presence of magic in the Greco-Roman world and and it´s practices among the Early Christians. Lastly, in the third and final moment, we will present our research on Simon within Early Christian Literature and historiography. However, we will focus in analysis in the Acts Apocryphal of Peter. Our intent is to show a new image from Simon. Not of a simple magician, but the image of a threatening leader of Christian hierarchical structures who has public acclaimed and used it to present himself as a new proposal for the Christian Community. We intend with this research to contribute with, a new perspective on the character Simon who is as important for Christian historiography as the other apostles.